Pembinaan Guru PAK dan Budi Pekerti terhadap Pembentukan Karakter Peserta Didik pada Masa Pandemi Covid-19 di Sekolah Dasar Katolik Pontianak - Lumban Tobing, Ona Sastri; Dwi Astuti, Florentina; Palupi Handayani, Exnasia Retno; G.P.H Meman, Oktavianey (Amare, 2022)
Society service (PKM) about PAK dan Budi Pekerti teachers training toward student’s character building during Covid-19 pandemic at catholic elementary school in Pontianak was an output of the previous research and was motivated by the education reality that is influenced by Covid -19 pandemic which caused the changing of the learning system from offline to online. The learning system changing influenced student’s character building where the PAK teachers could not educate the student’s character education directly at school. This training was aimed to give PAK dan Budi Pekerti Teachers guidance at catholic elementary school in Pontianak so that they always motivated and enthusiastic to do their duty and always attempt to teach the students by considering to the student’s character education during this Covid-19 pandemic.